Vendor Performance Monitoring in Automotive Manufacturing Under Localization Strategy - Wan Mahmood, Wan Hasrulnizzam; Kasim, Mohd; Azmi, Mohd; Salaam, Hadi; Razak, Mirasukma (Al-Khwarizmi Engineering Journal, 2026)
Given the competitive nature of the automotive industry, supplier performance must be analyzed and monitored to ensure continuous production while minimizing costs and maximizing quality and service. This research seeks to analyze the practices of vendor performance monitoring by non-Malaysian companies in localization strategies that align with national automotive policies. A case study was performed in ABC Company, a well-established Japanese vehicle manufacturer in Malaysia, through three main research approaches, namely, semistructured interview, site visit, and documentation review. The interview centered on their top management to understand how they monitor supplier performance and determine the current issues they face, while the site visit and documentation review focused on actual practices. A vendor known as WHN Company was chosen for additional analysis in the case study. Result reveals the poor performance of vendors with several root causes such as material shortages, manpower limitations, machine capacity issues, and financial constraints. A cause and effect analysis was performed to deeply understand the root causes. ABC terminates the existing vendors that have been classed in “C” category for 3 months and treated as underperformers. ABC then identifies and develops new qualified vendors to replace them. This case illustrates the importance of vendor monitoring, thorough assessment, and development for optimal performance. It also evaluates the importance of competitiveness and localization of the automotive sector’s strategies on supply chain resilience for sustaining adaptive monitoring mechanisms.